Changing myoglobin's paradigm: characterizing the role between lipids and myoglobin expression - Schlater, Amber E., author; Kanatous, Shane B., advisor; Florant, Gregory, committee member; Mykles, Donald, committee member; Bell, Christopher, committee member (Colorado State University. Libraries, 2014)
Myoglobin (Mb) is a muscular heme protein generally localized to oxidative muscle, where it functions to store and transport oxygen, as well as scavenge nitric oxide and reactive oxygen species (ROS). While the former role of Mb in oxygen storage/transport is undisputed in diving mammals and other hypoxia-adapted species, this function appears to be far more ambiguous in terrestrial, non-hypoxia-adapted species. During endurance exercise, terrestrial mammals rely on erythrocytic oxygen to fuel aerobic metabolism in working muscle. Physiological changes associated with endurance training elicit responses that increase muscular blood flow and subsequent oxygen delivery. Intramuscular oxygen stores, alternatively, appear to bear little significance in sustaining aerobic metabolism during endurance exercise, as evident by the inability to appreciably release intra-muscular stored oxygen during normoxic exercise; yet, terrestrial endurance athletes who tend to have a higher reliance on lipid-fueled metabolism have more Mb than their sedentary counterparts. Accordingly, Mb's traditional functional paradigm pertaining to oxygen storage and transport does not appear to be fully applicable to terrestrial mammals in vivo. Here, a series of datasets are provided offering alternative paradigm, where increases in Mb expression are associated with increases in lipid supplementation. C2C12 cells cultured in normoxic and hypoxic (0.5% oxygen) environments show increased Mb when supplemented with a 5% lipid mixture compared to glucose controls. While Mb regulatory pathways have been shown to involve Ca2+ signaling pathways via calcineurin (CN), this lipid-induced Mb stimulation is not affiliated with an increase in CN expression, suggestive of a regulatory pathway for Mb independent of Ca2+. Moreover, lipid-induced Mb stimulation parallels oxidative stress marker augmentation concomitant with Mb augmentation. Addition of antioxidant to lipid-supplemented cells reverses Mb increases, and acute exposure to H2O2 during hypoxic differentiation showed an increase in Mb relative to control cells, collectively suggesting a Mb regulatory pathway through redox signaling. Furthermore, comparison of two commonly used Mb assay techniques revealed that normoxic lipid-induced Mb increases are nearly explicitly oxidized, thus bearing important functional implications on Mb increases consequent of lipid stimulation. In light of these novel data and in conjunction with the inability of terrestrial mammals to appreciably utilize Mb oxygen stores during exercise, an alternative paradigm for Mb is proposed. I propose that the role of Mb as an antioxidant defense during terrestrial exercise, which increases lipid-based aerobic metabolism and ROS production, is more relevant and applicable than a role relevant to storage and transport of oxygen.
Keywords: C2C12; hypoxia; lipids; myoglobin; oxidative stress; skeletal muscle